Tribological and electrochemical properties of graphene - Francis Sunitha. (2011)
The report comprises the author’s research on a new method to synthesize graphene from amorphous carbon through annealing and its applications. The fabrication was done together with the fellow student mate, in which a series of experiments was carried out on nickel / diamond like carbon (DLC) bi layer coated in silicon (Si) & silicon dioxide (SiO2) /Si samples to find the optimum annealing parameters like temperature and time. At each stage, the samples were examined using Raman spectroscopy, particularly in terms of G & D peak positions and peak intensity.